CONSTRUCTIVE MODEL OF DATA STRUCTURES ADAPTATION IN RAM: PART I. PROGRAM TEXT CONSTRUCTING - Shynkarenko, V. I.; Zabula, H. V. (Science and Transport Progress, 2016)
Purpose. Rapidly growing volumes of information systems data being manipulated significantly reduce the temporary algorithms effeciency of their processing . Effective data layout in RAM is one of the directions of solving this problem. It is necessary to develop the model to solve problems of efficient automated data layout in RAM. Methodology. For processes simulation of data structures (DS) adaptation in RAM, the methodology of mathematical and algorithmic constructivism was applied. This approach involves the development of constructive and productive structures (CPS) with transformations of specialization, interpretation, specification and implementation. CPS development provides definition of expandable vector, signature of relations, transactions and constructive axioms. The most complex and essential part of the set of axioms is generated substitution rules that determine the output process of respective structures. Findings. CPS system was developed by the authors, consisting of the logical structure constructor of data, converters of logical structure in to a software interface and implementation in a programming language, constructors of scenarios and adaptation processes. The result of the adaptation process constructor is software text generations of the class library that implements the specified logical data structure with appropriate processing operations and its compilation in binary code. Originality. Structural model of development processes and data structures adaptation to different software and hardware environments was first proposed. It adapts date layout in the RAM and data processing algorithms. Application of constructivism in simulation allowed within a single approach and applied tools linking the data models and algorithms of their processing with performance criteria. Formation methodology of CPS system, mechanisms, and links between complementary CPS were improved. Modification of the constructor and converters allows changing and exploring the process of adaptation. Practical value. The developed model allows automating the data layout in RAM, which in turn increases the time efficiency of programs with significant processing of large and very large volumes of data.